Synergistic self-assembly of rod-like monomers in blue phase liquid crystals for tunable optical properties. Issue 37 (10th June 2022) - Pawale, Tejal; Cheng, Savannah; Hnatchuk, Nataliia; Li, Xiao
Abstract : The synergistic self-assembly behavior of the rod-like mesogenic monomers and the effects of their composition and concentration on the BP lattice are revealed during soft crystal growth and transformations, providing tunable photonic properties. Abstract : The three-dimensional nanostructures of blue phase liquid crystals (BPLCs) are becoming the spotlight of soft matter research in electro-optic devices, sensors, photonic crystals, and 3D lasers. The polymerization of the blue phase system overcomes the inherent thermal instability and paves the way for broadening the application of blue phases. Prior to polymerization, a fundamental understanding of the synergistic self-assembly behavior of monomers in the BP lattice can provide insights not only into the soft crystal growth and crystal transformations but also into the tunability of their optical properties. Here, we controlled the reactive monomer content in the BPs to observe the stability of BPI and BPII with different lattice dimensions before polymerization. The self-assembly behavior of commercially available rod-like mesogenic monomers in BP lattices with different monomer compositions was investigated under a homogeneous hybrid cell and directed self-assembly approach. The revealed synergistic self-assembly mechanism of the mesogenic monomer in BPs provides the ability to tune the photonic band gap of BP soft crystals.